2004
DOI: 10.1002/ccd.20242
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evaluation of the hemodynamic effects of atrial septal defect closure in adults with left ventricular dysfunction

Abstract: Transcatheter closure of atrial septal defects with left-to-right shunt induces an abrupt overload of the left ventricle that may cause acute heart failure in patients with left ventricular dysfunction. We report two cases of ostium secundum atrial septal defects associated with left ventricular dysfunction of different etiology. The hemodynamic evaluation of left ventricular function during transient abolition of the shunt with the sizing balloon of the Amplatzer system helped to establish the most correct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Several studies have suggested that development of acute congestive heart failure is due to abrupt elevation in left ventricular preload following transcatheter ASD closure, especially in elderly patients with impaired left ventricular systolic or diastolic function [3, 22, 23]. In our study, despite the fact that our patients had impaired left ventricular diastolic function estimated by decreased e ' and increased E / e ' [19, 20] as well as various comorbidities such as systemic hypertension, pulmonary artery hypertension and atrial fibrillation, acute congestive heart failure after the ASD closure did not develop in any of the patients except in one patient in whom the procedure was abandoned due to PCWP elevation during test balloon occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that development of acute congestive heart failure is due to abrupt elevation in left ventricular preload following transcatheter ASD closure, especially in elderly patients with impaired left ventricular systolic or diastolic function [3, 22, 23]. In our study, despite the fact that our patients had impaired left ventricular diastolic function estimated by decreased e ' and increased E / e ' [19, 20] as well as various comorbidities such as systemic hypertension, pulmonary artery hypertension and atrial fibrillation, acute congestive heart failure after the ASD closure did not develop in any of the patients except in one patient in whom the procedure was abandoned due to PCWP elevation during test balloon occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that development of acute congestive heart failure is due to abrupt elevation in left ventricular preload following transcatheter ASD closure, especially in elderly patients with impaired left ventricular systolic or diastolic function (6,24,25) In our experience, despite the fact that our patients had impaired left ventricular diastolic function estimated by decreased e' and increased E/e' (23,26) as well as various comorbidities such as systemic hypertension, pulmonary artery hypertension and atrial fibrillation, acute congestive heart failure after the ASD closure did not develop in any of the patients except in one patient in whom the procedure was abandoned due to PCWP elevation during test balloon occlusion. Schubert et al reported that peri-procedural anticongestive medication was effective in preventing congestive heart failure after ASD closure in elderly patients (27).…”
Section: Hemodynamic Features During Asd Closure In Geriatric Patientsmentioning
confidence: 99%
“…3,6) Several reports have described elderly patients with an ASD and LV dysfunction with CAD. 4,5,10) Bartel, et al reported a successful transcatheter ASD closure for a 67-year-old man with severe ICM (LVEF of 21%) resulting from two old myocardial infarctions, using anti-congestive therapies and balloon occlusion testing. 10) However, few reports have precisely evaluated volumes and function of both of the ventricles, including myocardial changes, before and after ASD closure using CMR, a more reproducible modality for assessing both of the ventricles compared to echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in ASD complicated with such severe LV dysfunction and CAD, to avoid the development of acute left HF and an increase in myocardial oxygen consumption following ASD closure, it is conceivable that coronary artery revascularization should be performed prior to ASD closure. 5,6) Onorato, et al reported successful sequential percutaneous coronary intervention (PCI) for CAD and transcatheter ASD closure in 6 cases with angina pectoris, where four patients underwent PCI prior to ASD closure. 13) Tomai, et al reported an unsuccessful case that developed acute left HF after a simultaneous approach of PCI and transcatheter ASD closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation